O professor inclusivo: uma invenção contemporânea - Pereira, Mônica de Fatima Silva Cavalcante (2014)
This dissertation seeks to highlight some of discursive practices that gave rise to the edge of certain kinds of knowledge about the ideal teacher to work with inclusive education, seeking to understand such practices and its effects of power / truth from the theories of Michel Foucault. For both operating with conceptions of governmentality, standardization and subjectivity, an analysis of two groups of materials: the first consisting of the Document and manuals produced by the Ministry of Education from 2001 to guide the formation of the inclusive teacher. The second concerns the legal provisions that were formatted in this period to standardize care to handicapped students. The main focus was the discussion about teacher education programs and the pitfalls and rule contained to produce an interesting teaching neoliberal subjectivity to gear them: docile, flexible, resilient and tolerant. From this analysis, it was possible to understand the formation of the Inclusive Teacher as an important state device (con) teacher training, whose condition of existence is founded on a risk prevention policy. This policy's main instruments exercise tolerance through awareness and subjectivity in ethics. Subjectivities are gestated by neoliberal governmentality, which emphasizes self-management, self-education and autorresponsabilização teachers at the various.